Reader participation, platform affordances, and interactive meaning-making in online literary environments - Suaidi (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
Background: The growth of online literary environments has transformed reading from a private act of textual reception into a participatory, interactive, and platform-mediated cultural practice in which readers comment, evaluate, classify, recommend, and circulate literary works. Objective: This study aims to examine how reader participation and interactivity are constructed through the relationship among digital narrative structures, reader responses, and platform affordances in online literary environments. Method: Using a qualitative digital textual design, this study analyzes digital literary works, reader comments, votes, kudos, bookmarks, tags, author’s notes, content warnings, interface features, and participation metrics from Electronic Literature Collection, Wattpad, Archive of Our Own, and ELMCIP Knowledge Base. Results: The findings show that interactive narrative structures operate through hyperlink-based navigation, multimodal activation, serial continuation, paratextual framing, and interface-mediated reader movement. Implication: Reader responses demonstrate that literary meaning is produced through affective engagement, interpretation, evaluation, communal interaction, curation, and textual circulation. Novelty: This study contributes to digital literary studies by integrating digital narratology, reader-response analysis, and platform/interface analysis into a unified framework for understanding online literature as a socio-technical literary ecology.